Bioluminescence of the Largest Luminous Vertebrate, the Kitefin Shark, Dalatias licha: First Insights and Comparative Aspects - Mallefet, Jérôme; Stevens, Darren W.; Duchatelet, Laurent (Frontiers in Marine Science, 2021)
Bioluminescence has often been seen as a spectacular yet uncommon event at sea but considering the vastness of the deep sea and the occurrence of luminous organisms in this zone, it is now more and more obvious that producing light at depth must play an important role structuring the biggest ecosystem on our planet. Three species of deepwater sharks (Dalatias licha, Etmopterus lucifer, and Etmopterus granulosus) were collected from the Chatham Rise, off New Zealand, and for the first time, we documented their luminescence. Comparison of glowing shark pictures, combined with histological description of light organs and hormonal control analysis, highlight the evolutive conservation of the bioluminescence process within Dalatiidae and Etmopteridae. A special emphasis is placed on the luminescence of D. licha, the largest known luminous vertebrate. This first experimental study of three luminous shark species from New Zealand provides an insight into the diversity of shark bioluminescence and highlights the need for more research to help understand these unusual deep-sea inhabitants: the glowing sharks.